On the Child's Right to Bodily Integrity: When Is the Right Infringed?. Issue 4 (5th July 2021) - Mazor, Joseph
Abstract: This article considers two competing types of conceptions of the pre-autonomous child's right to bodily integrity. The first, which I call encroachment conceptions, holds that any physically serious bodily encroachment infringes on the child's right to bodily integrity. The second, which I call best-interests conceptions, holds that the child's right to bodily integrity is infringed just in case the child is subjected to a bodily encroachment that substantially deviates from what is in the child's best interests. I argue in this article that best-interests conceptions are more plausible than encroachment conceptions. They have more attractive implications regarding the permissibility of interventions in children's bodies that are beneficial for the child but are not medically necessary. They are better able to explain the moral distinction between cases in which an encroachment on a child's body is needed to benefit that child and cases in which an encroachment on one child's body is needed to benefit another. Finally, best-interests conceptions are more consonant than encroachment conceptions with our understanding of adults' right to bodily integrity.